Hadith #2851 - Sunan Abi Dawud - Abu Idrees al-Khulani أبو إدريس الخولاني; Abu Tha'laba al-Khushni; Bsr bin 'Ubaidullah بسر بن عبيد الله الحضرمي; Da'ud bin 'Amr bin Zuhayr داود بن عمرو الضبي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان (Sunan Abi Dawud)
The Prophet (ﷺ) said: Eat what ever is caught for you by a dog or a hawk you have trained and set off when you have mentioned Allah’s name. I said: (Does this apply) if it killed (the animal)? He said: When it kills it without eating any of it, for it caught it only for you. Abu Dawud said: If a hawk eats any of it, there is no harm (in eating it). If a dog eats it, it is disapproved (to eat the meat). If it drinks blood, there is no harm (in eating it).
Grade: Da'if

Hadith #2860 - Sunan Abi Dawud - Abu Tha'laba al-Khushni; Hmad bin Khalid al-Khyat حماد بن خالد الخياط القرشي; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) said: He said: He who sticks to a king is perverted. This version adds: The nearer a servant (of Allah) goes to a king, the farther he keeps away from Allah.
Grade: Da'if

Hadith #3801 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Idrees al-Khulani أبو إدريس الخولاني; Abu Tha'laba al-Khushni; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
I asked the Messenger of Allah (ﷺ) about the hyena. He replied: It is game, and if one who is wearing ihram (pilgrim’s robe) hunts it, he should give a sheep as atonement.
Grade: Sahih

Hadith #3838 - Sunan Abi Dawud - Abdullah bin al-'Ala' عبد الله بن العلاء بن زبر; Abu Tha'laba al-Khushni; Muhammad bin Shu'aib bin Shabur محمد بن شعيب بن شابور; Nsr bin 'Asim al-Lythy نصر بن عاصم الليثي البصري (Sunan Abi Dawud)
I was on an expedition along with the Messenger of Allah (ﷺ). We got the vessels and skins of the polytheists and used them. But he did not object to them (i.e. us) for that (action).
Grade: Sahih

Hadith #4347 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Jbyr عبد الرحمن بن جبير المصري; Abu Tha'laba al-Khushni; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
The people will not perish until their sins and faults become abundant, and there remains no excuse for them.
Grade: Sahih